Practical data analysis and reporting with BIRT : use the open-source Eclipse-based business intelligence and reporting tools system to design and create reports as quickly as possible /: use the open-source Eclipse-based business intelligence and reporting tools system to design and create reports as quickly as possible. (2008) - Unknown
No abstract available